Muon $$g-2$$ g - 2 anomaly from vector-like leptons in a 2-Higgs-doublet + scalar singlet model - Tim Brune; Thomas W. Kephart; Heinrich Päs (European Physical Journal C: Particles and Fields)
Abstract We revisit an economical model for the $$g-2$$ g - 2 anomaly featuring a vector-like charged fermion, a scalar doublet and a scalar singlet in the light of new results from Fermilab. The phenomenological implications for lepton-flavor universality, Higgs decays, and charged lepton-flavor violating decays are discussed in detail.